MEMBANGUN MINAT BELAJAR SISWA GENERASI Z MELALUI INOVASI DIGITAL DALAM MATERI PENDIDIKAN AGAMA ISLAM - Viona Hernanda Fatikhasari; Hamdan Nur Diansyah; Siti Halimah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Islamic Religious Education (PAI) has an important role in distinguishing the traits and characteristics of the younger generation. However, the rapid advancement of information technology, especially among Generation Z, requires more innovative and relevant teaching strategies. The purpose of this article is to create an effective digital literacy-based educational worldview for Generation Z in PAI. Through simulation and visualization, technology enables the development of more keys in educational materials and helps students understand Islamic concepts. In education, personalization allows educational modules and teaching strategies to be tailored to students' needs, which can increase their motivation and learning outcomes. This phenomenon is very similar to the development of Generation Z in the digital world.